Living with Monsters (Punctum Books, 2023)
For every generic type of monster—ghost, demon, vampire, dragon—there are countless locally specific manifestations, with their own names, traits, and appearances. Such monsters populate all corners of the globe haunting their humans wherever they live. Living with Monsters is a collection of fourteen short pieces of ethnographic fiction (and a more academically inclined introduction and afterword) presenting a playful, spirited, and engaging look at how people live with their respective monsters around the world. They focus on the nitty-gritty dos and don’ts of how to placate spirits in India; how to domesticate Georgian goblins, how to live with aliens, how to avoid being taken by Anito in Taiwan, while simultaneously illuminating the politics of monster–human relations.